Effect of ethanolic extract of Aloe vera gel on certain common clinical pathogens - Halima Begum; Sadia Choudhury Shimmi; Mahfuza Mazeda Rowshan; Sayeda Khanom (Penerbit UMS, 2016)
Antimicrobial activity of ethanolic extract of Aloe vera were observed against Staphylococcus aureus, Staphylococcus pyogenes, Staphylococcus saprophyticus, Streptococcus pneumonia and Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae. Aloe vera leaf gel was used for ethanolic extraction. Zones of inhibition in millimeter was used to measure the antimicrobial effect. Antimicrobial susceptibility test showed that ethanolic extract has growth inhibitory effects against the tested pathogens. Ethanolic extract of Aloe vera has growth inhibitory effects against tested pathogen seen by antimicrobial susceptibility testing.